Possibility to Use Low Temperature Pulsed RF Sputtered Indium Tin Oxide for the Fabrication of Organic Solar Cell. (23rd May 2013) - Middya, Somnath; Layek, Animesh; Ray, Partha Pratim
Abstract : In this work we have used pulsed RF sputtering method to deposit indium tin oxide (ITO) for the fabrication of P3HT:PCBM based bulk heterojunction polymer solar cell. We have deposited ITO at low substrate temperature (100°C) and for different pulse modes. Oxygen was used as an admixture to the sputtering gas argon, and the percentage was varied from 0 to 6%. During deposition, plasma was studied by optical emission spectroscopy (OES) method. For our present range of deposition conditions lowest resistivity of ITO is around 2 × 10 −4 Ω-cm, and it is deposited in High-Low mode with 1% of oxygen added to argon. The effect of oxygen admixture on electrical and optical properties of ITO thin films has been studied for different pulse modes. ITO films have been optimised by measuring their resistivity, transparency, and X-ray diffraction. Finally we have applied the ITO film for the fabrication of P3HT:PCBM based solar cell.